Ocean wave height inversion under low sea state from horizontal polarized X-band nautical radar images. Issue 1 (2nd January 2021) - Wang, Li; Hong, Lijuan
ABSTRACT: A SWH model under low sea state is established, the model is based on the information contained in the wave field to extract the deviation between the kurtosis of the Weibull distribution and the kurtosis of the radar image sequence under low sea state firstly. Then, a linear relationship is established to retrieve the SWH under low sea state from the combination of the deviation and the apparent characteristics ratio of the sea surface roughness. Lastly, the SWH derived by using this proposed method matches better with that measured by an in situ buoy nearby under very low sea state.